Outcomes and opportunities: a nurse-led model of chronic disease management in Australian general practice - Eley, D.; Patterson, E.; Young, J.; Fahey, P.; Del Mar, C.; Hegney, Desley; Synnott, R.; Mahomed, R.; Baker, P.; Scuffham, P. (The Australian Journal of Primary Health, La Trobe University, 2012)
The Australian government’s commitment to health service reform has placed general practice at the centre of its agenda to manage chronic disease. Concerns about the capacity of GPs to meet the growing chronic disease burden has stimulated the implementation and testing of new models of care that better utilise practice nurses (PN). This paper reports on a mixed-methods study nested within a larger study that trialled the feasibility and acceptability of a new model of nurse-led chronic disease management in three general practices. Patients over 18 years of age with type 2 diabetes, hypertension or stable ischaemic heart disease were randomised into PN-led or usual GP-led care. Primary outcomes were self-reported quality of life and perceptions of the model’s feasibility and acceptability from the perspective of patients and GPs. Over the 12-month study quality of life decreased but the trend between groups was not statistically different. Qualitative data indicate that the PN-led model was acceptable and feasible to GPs and patients. It is possible to extend the scope of PN care to lead the routine clinical management of patients’ stable chronic diseases. All GPs identified significant advantages to the model and elected to continue with the PN-led care after our study concluded.